Pharmacoeconomic feasibility of using the drug Hemangiol (propranolol, oral solution) in the treatment of proliferating infantile hemangioma requiring systemic therapy - I. N. Dyakov; S. R. Varfolomeеva (IRBIS LLC, 2021)
Aim. The study aimed to evaluate the pharmacoeconomic feasibility of propranolol application in the dosage form of the oral solution in the treatment of proliferating infantile hemangioma requiring systemic therapy.Materials and methods. The study design was a retrospective analysis of the published data. The methods of pharmacoeconomic analysis included a clinical-economic analysis (cost-effectiveness analysis) with a sensitivity analysis; and a "budget impact" analysis with a sensitivity analysis. The authors compared the pharmacoeconomic effectiveness of pharmacotherapy for infant hemangiomas with propranolol and surgical methods of treatment.Results. The efficacy of propranolol therapy was 39% higher than surgical methods of treatment. The relative increase in the efficacy of propranolol therapy compared to surgical treatments was 68.4%. At the same time, the cost of propranolol therapy was lower than the cost of surgical treatments by 31.7% or 56,486,07 RUR per patient per year. The application of propranolol in the treatment for proliferating infantile hemangioma allowed reducing the burden on the budget of the state guarantee program in comparison with surgical methods of treatment for 3 years by 1,562.0 million RUR with a proportion of 12% of patients with infant hemangiomas requiring systemic therapy (9,694 patients per year). The sensitivity analysis of the cost and effectiveness of the compared medical technologies showed that the obtained results are resistant to the fluctuations in these parameters in the range from − 20% to + 20%.Conclusion. The application of propranolol preparation in a dosage form of oral solution for the treatment of patients with proliferating infantile hemangioma will significantly increase the efficiency of therapy and reduce costs associated with the application of surgical methods of treatment.